Magical women: Representations of female characters in the Witcher video game series. (October 2022) - Heritage, Frazer
Abstract: Several videogames allow players to form their own narratives by making the player choose certain options with different dialogues and thus different representations. This can be problematic when exploring the representation of gender from the perspective of player's experiences. I argue that one way to overcome this is to use corpus linguistic methods. In this paper, the videogame series The Witcher (CD Projekt Red 2007, 2011, 2015 ) is taken as a case study for lexico-grammatical analysis of the representation of gender via corpus methods. Keyword analysis shows that male characters are more likely to occur than female characters and have a more diverse range of professions than female characters. I argue that the main female characters of the game are typically sorceresses, and so I explore how this term is used across the corpus. The analysis demonstrates that sorceresses are represented as educated and intelligent, but subject to a glass ceiling effect: they are only ever advisors and not leaders. I argue that regardless of what options players choose, they are statistically more likely to encounter these problematic representations of gender, thus raising questions about whether it is possible to escape sexist discourses in this medium.